Blind Belt using Ultrasonic Sensor - Arwinanto Sitohang; Ignatius Visnu; Indra Eka Prayoga; Erwin Sitompul; Hendra J. Tarigan (President University, 2020)
Vision impairment has been common phenomena in this day and age. Many people suffer from this impairment with only a few technological supports to help them in daily life. This project created prototype to help people with vision impairment navigating through space. Built in the form of a belt, this project uses Ultrasonic sensor to detect the surrounding object. It uses three ultrasonic sensors attached to the front, left, and right area of the belt. Whenever an object is detected near any of these three areas, buzzer will be ringing. The buzzer is set in three different tones such that the wearer knows which side of the belt the object is.